Analysis of the Impact of Indirect Taxation on Foreign Direct Investment Inflows in Malaysia: Implications for Sustainable Economic Growth - Razali, Tengku Rafidatul Akma Tengku; Masron, Tajul Ariffin; Kamarudin, Mohd Hafez; Beleya, Prashanth; Chelliah, Mahendra Kumar (Journal of Posthumanism, 2025)
Despite Malaysia’s reputation as one of the most attractive destinations for FDI in Asia, the nation has experienced a downward trend in FDI flows since reaching a peak in 2011. A well-structured taxation system is a key strategy for attracting FDI, and Malaysia has recently undergone significant reforms in its indirect tax policies. This study examines the effectiveness of these tax changes in influencing foreign investment decisions by focusing on five key indirect tax. Utilizing annual tax revenue data from the Royal Malaysian Customs Department for the period 1999–2023, this study applies the Autoregressive Distributed Lag model to estimate the impact of various indirect taxes on FDI inflows. The findings reveal that import duty and consumption tax negatively affect FDI inflows, while export duty, excise duty, and vehicle levy have a positive impact on FDI inflows into Malaysia. These results underscore the importance of tax policy design in shaping FDI trends. To enhance Malaysia’s investment attractiveness, policymakers should consider reducing import duties and consumption tax, while maintaining or optimizing revenue-generating taxes such as export duties, excise duties, and vehicle levies. This study provides valuable insights for tax authorities and policymakers in formulating effective fiscal strategies to sustain Malaysia’s competitiveness as a preferred FDI destination.